COVID-19 in a Subset of Hospitalized Children in Israel. (15th June 2021) - Ben-Shimol, Shalom; Livni, Gilat; Megged, Orli; Greenberg, David; Danino, Dana; Youngster, Ilan; Shachor-Meyouhas, Yael; Dabaja-Younis, Halima; Scheuerman, Oded; Mor, Meirav; Somekh, Eli; Yakub Hanna, Husam; et al.
Abstract: Background: Most pediatric coronavirus disease 2019 (COVID-19) is mild. We assessed nationally severe COVID-19, including pediatric inflammatory multisystem syndrome (PIMS), in hospitalized children. Methods: An ongoing, prospective, national surveillance was conducted from March 2020 through March 2021, at 20 hospitals treating children <18 years across Israel (~75% of Israeli hospitals). Results: Overall, 1007 cases (439 outpatients and 568 hospitalized) identified represent 0.35% of pediatric COVID-19 nationwide (n = 291 628). Of hospitalized cases, 464 (82%), 48 (8%), and 56 (10%) had mild, moderate/severe, and PIMS disease, respectively. The mean ± SD age was 5.6 ± 6.4 years. In mild, moderate/severe, and PIMS disease, 55%, 23%, and 4% of patients were <1 year old, respectively. Obesity was reported in 1%, 4%, and 13% of patients, respectively ( P < .001). The most common symptom was fever in 67%, 60%, and 100%, respectively, whereas respiratory symptoms were documented in 33%, 41%, and 38% of patients, respectively. Lymphopenia was recorded in 25%, 60%, and 86% of cases, respectively. PIMS diagnosis was mainly serology-based (in 59%). Gastrointestinal symptoms, cardiovascular involvement, rash, and conjunctivitis were noted in 82%, 61%, 57%, and 34% of PIMS episodes, respectively. Elevated C-reactive protein (100%), ferritin, troponin, D-dimer, low albumin, and thrombocytopenia were common in PIMS. Echocardiography revealed pathological findings in 33% of patients. PIMS mainstay treatment included corticosteroids (77%) and intravenous immunoglobulin (53%). No mortality was recorded. Conclusions: At a national level, pediatric COVID-19 is mild, even in hospitalized cases, with only a third presenting with respiratory involvement. PIMS is rare, but necessitates a high index of suspicion, and with suitable treatment prognosis is favorable. Abstract : We assessed pediatric COVID-19 in 20/26 Israeli hospitals. Overall, 568 cases (82% mild disease, 8% moderate/severe disease, and 10% PIMS), representing <1% of pediatric SARS-CoV-2 infections nationwide, were identified. Lower respiratory tract infection symptoms were documented in 13% of patients.